The Impact of Price And Social Media on Buying Decisions - Frans Sudirjo; Dian Artanti Arubusman; Josua Sahala; Edhie Budi Setiawan; Zaenal Abidin (Al-Kharaj: Journal of Islamic Economic and Business, 2023)
The goal of this study was to ascertain how consumer purchasing choices at Warung Selasih Kadungora Garut were influenced by price, café ambiance, and social media. In this study, data were gathered using the Accidental Sampling technique using a questionnaire with 91 respondents. The research used a quantitative approach together with a descriptive examination of case studies. Data analysis used normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests utilizing Durbin Watson tests, and hypothesis testing to identify which variables had a meaningful link. Validity and reliability tests were applied to data instruments. The partial t-test produced a tcount price variable of 0.867 1973 and a significant value of 0.242 > 0.05, showing that the test was not significant. Then, Ho is approved while Ha is turned down. A significant value was 0.342 > 0.05, suggesting that the cafe atmosphere variable is not significant. The cafe atmosphere variable received 15 tcount from the t-test (partial) computation, and it was 0.834 1.873. Additionally, the social media variables obtained from the partial t-test calculation produced the values 6.174> 1.873 for the tcount social media variables and a significant value of 0.000 0.05, indicating significant.